Student perceptions of technological tools for flipped instruction: The case of Padlet, Kahoot! and Cirrus - Dianati, Seb; Nguyen, Mai; Dao, Phung; Iwashita, Noriko; Vasquez, Claudia (Journal of University Teaching and Learning Practice, 2020)
Technological tools used in teaching and learning have been reported to influence their satisfaction, engagement and their continued effort in learning (Roach, 2014). The present study, therefore, investigated students’ perceptions of technological use in a flipped classroom at university level through evaluation of three different web-based tools, using the lens of the Technology Acceptance Model (TAM) (Davis, 1989; Venkatesh & Davis, 2000). These tools include a collaborative canvas tool (Padlet), a live polling platform (Kahoot!) and an annotation tool (Cirrus). Results from focus group interviews show that most of the students had positive perceptions of the three technological tools targeted in this study. Nevertheless, using the TAM model that draws on two indexes, namely usefulness and perceived ease of use, the findings revealed students’ mixed perceptions towards the three tools. Particularly, Padlet was perceived to be useful for both independent and colloborative learning, but less easy to use when there was too much content. Kahoot! was considered the most useful and easy to use for revision of learnt concepts. Finally, Cirrus was easy to use, but less useful for creative tasks. The results are discussed in terms of the role of technological tools in flipped learning, and implications for technologically enhanced flipped instruction are suggested.